Muslim students’ perceptions of post-pandemic learning in Malaysia / Sheela Faizura Nik Fauzi, Noor Muthaah Mohamad Ali Adaha and Miranti Eka Puteri - Nik Fauzi, Sheela Faizura; Mohamad Ali Adaha, Noor Muthaah; Miranti Eka Puteri (Academy of Contemporary Islamic Studies (ACIS), Universiti Teknologi MARA (UiTM), 2025)
The COVID-19 pandemic reshaped education, accelerating the adoption of online and hybrid learning. For Muslim students, this transition required balancing academic demands with religious principles. While online learning offers flexibility and diverse resources, challenges such as maintaining discipline, engagement, and religious commitments persist. Limited research explores how Islamic values influence Muslim students' adaptation to post-pandemic learning. This study examines their perceptions, focusing on opportunities, challenges, and coping mechanisms rooted in Islamic teachings. This study investigates Muslim students’ experiences with post-pandemic learning, emphasizing Islamic elements. A structured questionnaire was used to collect data on students’ backgrounds, learning perceptions, and challenges. A quantitative analysis, including mean, median, and frequency calculations, was applied. The study sample comprised Muslim students from Malaysian universities with diverse socio-cultural backgrounds and educational levels. Findings reveal that most Muslim students perceive post-pandemic learning positively, aligning with Islam’s emphasis on knowledge-seeking. They appreciate online learning for its flexibility, access to global resources, and the development of independent learning skills. Technology also facilitates engagement with scholars and peers, broadening their understanding of Islamic teachings. However, transitioning to online learning posed challenges, including motivation, time management, and social isolation. Many students relied on Islamic principles, such as patience, perseverance, and reliance on Allah SWT, to navigate these difficulties. They maintained structured routines, set academic goals, and practiced self-discipline, reflecting Islamic teachings on personal growth and discipline. Muslim students have demonstrated resilience in adapting to post-pandemic learning while upholding Islamic values. By addressing their challenges and enhancing supportive learning environments, post-pandemic education can better integrate Islamic principles, ensuring both academic success and spiritual well-being. Understanding these perspectives will help create inclusive educational models that cater to Muslim students' needs.